Wybrane aspekty przekładu terminów prawnych w kontekście międzykulturowym w postępowaniu ekstradycyjnym między Niemcami a Polską - Bawej, Izabela (Acta Neophilologica, 2021)
This paper focuses on the problem of cultural differences with respect to legal terms translation concerning the extradition procedure between Germany and Poland. In this context, the question as to how to tailor German legal terminology referring to institutional and office names to that of the Polish language in order to make the text comprehensible and understandable for Polish readers, e.g., judges, prosecutors or legal representatives, will be considered from a cultural perspective. The study is illustrated by examples from a German prosecutor’s letters to the Polish District Court regarding extradition arrangement.